Overdose, opioid treatment admissions and prescription opioid pain reliever relationships: United States, 2010–2019 - Aubry, Larry; Carr, B. Thomas (Frontiers in Pain Research, 2022)
Relationships of Prescription Opioid Sales to Opiate Treatment Admissions and Overdose Deaths: A Reanalysis of Relationships -- United States 2010-2019 Background: In 2016, the United States Centers for Disease Control and Prevention (CDC) issued “CDC Guideline for Prescribing Opioids for Chronic Pain”. The guideline used data from 1999 to 2010 that related Opioid Sales to Opiate Treatment Admissions (a measure of drug addiction rates) Opioid Deaths. The CDC’s analysis indicated that opioid prescriptions are directly correlated1-8 with drug addiction and overdose mortality outcomes. As a result, prescription opioid sales have been curtailed, making it difficult for sufferers of severe chronic pain to access an effective treatment option. In this paper, the relationships between opioid sales, drug addiction, and opioid deaths are reexamined using data from 2010 to 2019. Methods: Linear regression models were fit to each response separately. Opioid sales (measured as MME per capita) was the independent variable. Total overdose deaths (TOD), any opioid overdose deaths (AOD), prescription opioid overdose deaths (POD) and opiate treatment admissions (OTA) were the dependent, response variables. The models were assessed using three criteria: the statistical significance of the model (Overall P-Value), the quality of the fit (R2), and the sign of the slope coefficient. Results: The analyses revealed that the direct correlations (significant, positive slopes) reported by the CDC based on data from 1999 to 2010 no longer exist based on data from 2010 to 2019. The relationships either have reversed (i.e., significant negative slopes) or are non-existent (no significant model). Conclusions: The basis for the CDC guideline no longer holds. The guideline should be updated or annulled based on the current relationships that have existed for a decade. This is especially relevant for people suffering from severe, chronic pain, whose access to prescription opioids has been severely curtailed under the current guideline and to ensure that government resources are directed to an effective approach to reducing overdose deaths.